2009
DOI: 10.4103/0019-5359.55884
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 gene polymorphisms contribute to coronary artery disease risk among north Indians

Abstract: 70). These odds ratios were higher in the sub-sample of smokers (2.84 and 1.45, respectively). Binary logistic regression analysis also confirmed that *R allele carriers (QR and RR) have a higher risk of CAD (OR= 3.54,). PON1-55 locus did not show significant differences between patients and controls, but LL genotype and *L allele were significant risk factors in the nonsmoker group. RL haplotype was also significantly associated with CAD risk (OR= 1.44,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Our results agreed with earlier studies showing that PON1-55 independently has no consequence on CAD [10, 30, 40]. Contrariwise, a study proposed the protective effect of the M allele of PON1 against CAD [48].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results agreed with earlier studies showing that PON1-55 independently has no consequence on CAD [10, 30, 40]. Contrariwise, a study proposed the protective effect of the M allele of PON1 against CAD [48].…”
Section: Discussionsupporting
confidence: 83%
“…Some of the studies that were accomplished to demonstrate the relationship between the PON1-L55M polymorphism and CAD showed conflicting results [51]. In an Austrian population, it was seen that the L55M polymorphism was linked with CAD [49], whereas studies in other populations showed inconsistent results [30]. Our study showed a negative correlation between the L55M locus and CAD risk, and only the M allele was concluded to be a risk allele.…”
Section: Discussionmentioning
confidence: 59%
“…Another paper analyzed PON1 192 and 55 polymorphisms in the etiology of CAD. The authors failed to find an association between PON1 55 polymorphism and the onset of cardiovascular disease, but they found that LL genotype and L allele were significant risk factors in the nonsmoker group [16]. Accordingly to this study, Malin et al [17] also have found that in nonsmoking men the LL genotype could represent a genetic risk factor for carotid artery atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 68%
“…For this purpose, previous studies have assessed the interactions between a limited number of coding variants in PON1 and cigarette smoking status on the risk of CHD. However results have been inconclusive [15,16]. For example, a study in the Costa Rican population showed a significant interaction between the rs662 v ariant and smoking status to modify CHD risk [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the C allele at rs662 was reported to increase the risk of CHD in non-smokers only. However, another study conducted in a different ethnic group (Asian-Indians) indicated contrasting results for the same PON1 SNP (rs662), in which the risk allele (C allele) was associated with increased CHD risk among smokers [16]. …”
Section: Introductionmentioning
confidence: 99%